Macrocyclic inhibitors of 3C and 3C-like proteases of picornavirus, norovirus, and coronavirus - Mandadapu, Sivakoteswara Rao; Weerawarna, Pathum M.; Prior, Allan M.; Uy, Roxanne Adeline Z.; Aravapalli, Sridhar; Alliston, Kevin R.; Lushington, Gerald H.; Kim, Yunjeong; Hua, Duy H.; Chang, Kyeong-Ok; Groutas, William C. (My University, 2013)
The design, synthesis, and in vitro evaluation of the first macrocyclic inhibitor of 3C and 3C-like proteases of picornavirus, norovirus, and coronavirus are reported. The in vitro inhibitory activity (50% effective concentration) of the macrocyclic inhibitor toward enterovirus 3C protease (CVB3 Nancy strain), and coronavirus (SARS-CoV) and norovirus 3C-like proteases, was determined to be 1.8, 15.5 and 5.1 μM, respectively.
Keywords: Proteases; Picornavirus; Norovirus; Coronavirus; Macrocyclic inhibitors